A pilot randomised trial of catheter-directed thrombolysis or standard anticoagulation for patients with intermediate-high risk acute pulmonary embolism - Kroupa, Josef; Buk, Michal; Weichet, Jiri; Malikova, Hana; Bartova, Lucie; Linkova, Hana; Ionita, Oana; Kozel, Martin; Motovska, Zuzana; Kocka, Viktor (EuroIntervention, 2022)
BACKGROUND: Intermediate-high risk acute pulmonary embolism (PE) remains associated with substantial mortality despite anticoagulation therapy. AIMS: The aim of this randomised pilot study was to compare catheter-directed thrombolysis to standard anticoagulation therapy. METHODS: Intermediate-high risk acute PE patients were admitted to a tertiary care centre (November 2019 to April 2021) and randomised in a 1:1 ratio to catheter-directed thrombolysis (CDT) or standard anticoagulation. Two catheters were used for the infusion of alteplase (1 mg/hr/catheter; total dose 20 mg) in the CDT group. The primary efficacy endpoint targeted improvement of right ventricular (RV) function, a decrease in pulmonary pressure, and a reduction of thrombus burden. RESULTS: Twenty-three patients were included (12 in the CDT group and 11 in the standard care group). The primary efficacy endpoint was achieved more frequently in the CDT group than in the standard care group (7 of 12 patients vs 1 of 11 patients, p=0.0004). An RV/left ventricular ratio reduction ≥25% (evident on computed tomography angiography) was achieved in 7 of 12 patients in the CDT group vs 2 of 11 patients in the standard care group (p=0.03). A systolic pulmonary artery pressure decrease of ≥30% or normotension at 24 hrs after randomisation was present in 10 of 12 patients in the CDT group vs 2 of 11 patients in the standard care group (p=0.001). There was no intracranial or life-threatening bleeding (type 5 or 3c bleeding, according to the Bleeding Academic Research Consortium classification). CONCLUSIONS: CDT for intermediate-high risk acute PE appears to be safe and effective. Further research is warranted to assess clinical endpoints.
Keywords: plicní embolie; Tissue Plasminogen Activator; krvácení; katétry; výsledek terapie; Catheters; fibrinolytika; lidé; Thrombolytic Therapy; Pulmonary Embolism; Acute Disease; akutní nemoc; Fibrinolytic Agents; Pilot Projects; antikoagulancia; Treatment Outcome; trombolytická terapie; Anticoagulants; Humans; tkáňový aktivátor plazminogenu; pilotní projekty; Hemorrhage